Design and implementation of web application for aphasia training - Lim, Bing Hong (Nanyang Technological University, 2024)
Aphasia, a language disorder brought on by injury to a specific region of the brain that regulates language understanding and expression. It presents a substantial challenge to effective communication and quality of life. Current issues with aphasia therapy include the high cost of sessions, a shortage of available therapists, and the inconvenience associated with traveling to therapy appointments. To tackle these challenges, SpeakNow, an aphasia speech therapy application, was developed to offer a personalized and accessible alternative to traditional therapy.